Preparation and reshaping of composite microparticles for color toner based on the encapsulated nanoparticles. Issue 47 (9th June 2020) - Liao, Jun; Ye, Mingquan; Han, Aijun; Chen, Xin; Zhang, Kui; Guo, Jianming; Chen, Chenlu
Abstract: In this paper, the styrene–acrylic resin‐encapsulated organic pigment composite nanoparticles were synthesized by mini‐emulsion polymerization first, and then the aggregated microparticles used for color toner were prepared via the emulsion aggregation method. Transmission electron microscopy, dynamic light scattering, and zeta potential analysis manifest that when the emulsifier dosage was 5 wt% of the monomer, the composite nanoparticles owned clearly core‐shell structure, uniform size, and appropriate zeta potential, which was conducive to the subsequent aggregation. The evolution of aggregated particle size and morphology under different stirring rates, coagulant concentrations, and temperatures was investigated by mastersizer and scanning electron microscopy. The result shows that when the stirring rate was 1, 000 rpm, coagulant concentration was 0.2 mol/L, and the curing temperature was 65°C, aggregated particles with suitable size, narrow size distribution, and regular shape could be obtained. The reshaping of aggregated particles can further improve their morphology. When the reshaping temperature was 75°C, the product particles owned perfect spherical shape, and there were almost no cracks and pores on the surface of the particles. This synthesis strategy is believed to provide a guide for the fabrication of composite microparticles with controllable particle size and morphology. Abstract : Preparation of color toner particles with core‐shell structure via mini‐emulsion polymerization and the emulsion aggregation method.